TINJAUAN HUKUM PIDANA TERHADAP PELAKU UJARAN KEBENCIAN (HATE SPEECH) DALAM MASA KAMPANYE DI INDONESIA - nur alim (Datuk Sulaiman Law Review (DaLRev), 2025)
This study aims to determine the legal regulations in Indonesia against hate speech crimes through social media and the views of Islamic Law on Hate Speech Crimes. This study uses a normative legal research method with a comparative approach supported by data obtained through library research. The results of the study indicate that the provisions stipulated in Law Number 11 of 2008 concerning Information and Electronic Transactions have explained the limitations and things that a person may and may not do on social media. Islam provides ta'zir punishment for perpetrators of insults, defamation and the like. Ta'zir crimes are crimes whose forms and punishments are determined by the government, which do not conflict with the principles, values ​​and objectives of sharia. While in Indonesian law, insults and/or defamation through social media, the explanation of the punishment is contained in Article 27 paragraph (3) of the ITE Law.